Cowden syndrome complicated by a gastrointestinal stromal tumor. Issue 5 (30th September 2013) - Nakamura, Masanao; Hirooka, Yoshiki; Yamamura, Takeshi; Yamada, Koji; Nagura, Asuka; Yoshimura, Toru; Ohmiya, Naoki; Uehara, Keisuke; Yoshioka, Yuichiro; Nagino, Masato; Goto, Hidemi
<x xml:space="preserve">Abstract</x> To our knowledge, this is the first report of Cowden syndrome complicated by a gastrointestinal stromal tumor (GIST) of the small bowel. A 42‐year‐old female patient was found to have an abdominal mass that was diagnosed as the cause of anemia and was surgically extracted. The surgical specimen was found to be a GIST. During the same period, the patient underwent an endoscopic examination of the entire gastrointestinal tract. She was also diagnosed as having Cowden syndrome based on gastrointestinal polyps and skin, thyroid and breast lesions. Cowden syndrome is associated with germline mutations in the tumorsuppressor gene PTEN. PTEN expression may be essential to tumor growth and is a predictive biomarker of the prognosis of both diseases. The present report of such a case is expected to further the analysis of Cowden syndrome.